Influence of Immobilization Time on Functional Outcome in Radial Neck Fractures in Children - Badoi, Adina; Frech-Dörfler, Martina; Häcker, Frank-Martin; Mayr, Johannes (European Journal of Pediatric Surgery, 2016)
Background Radial neck fractures represent 20 to 30% of elbow fractures in children. Incorrect treatment can lead to significant permanent functional impairment. Posttraumatic avascular necrosis may cause a deformity of the radial head and neck. Deformation of the radial head and neck can be more severe after open rather than closed reduction or orthopedic treatment without reduction. The aim of our study was to analyze the influence of immobilization time on functional outcome.Patients and Methods Retrospective, descriptive study of all children who had been treated for a radial neck fracture between 1999 and 2013 at the University Children's Hospital Basel. Patients were allocated to two groups (group 1: patients treated between 1999 and 2008, group 2: patients treated between 2009 and 2013). The fractures were classified according to the classification of Metaizeau. The primary endpoint was the percentage of patients who reached the full range of elbow motion at the end of the treatment period or the last follow-up. Secondary endpoints were immobilization time and number of patients with persistent physical restrictions of the elbow range of motion as well as the type of restrictions and subjective complaints.Results A total of 67 patients treated for radial neck fracture were included in the first group (1999–2008). A total of 47 patients were allocated to the second group (2009–2013). Overall, 59 patients in group 1 and 39 patients in group 2 were treated nonoperatively. Average immobilization time was 22.7 days (range, 6–60 days) in group 1 and 13.2 days (range, 0–27 days) in group 2. Full range of motion was observed in 50 to 72.7% of patients in group 1 and in 71.4 to 92% of patients in group 2, depending on the grade of fracture displacement. Overall, 21 patients (31%) of group 1 showed a persistent functional restriction. In group 2, only six patients (12%) suffered from a persistent functional restriction of the elbow range of motion.Conclusion Aside from the severity of fracture displacement and treatment modality (conservative vs. operative, closed vs. open reduction), the duration of immobilization may also influence the functional outcome. Further prospective studies are required to confirm our results.
Keywords: radial neck fractures; functional outcome; immobilization time; children